Evaluación de la concentración de material particulado pm10 y pm2.5 en la Parroquia Ignacio Flores de la Provincia de Cotopaxi en el periodo 2018–2019 - Taguada Tenorio, Jenny Maricela (2019)
The present investigation was developed with the objective of evaluating the concentration of PM10 and PM2.5 particulate material in the Ignacio Flores parish of the Latacunga canton, to determine if it was generating atmospheric impacts in these places, produced by emission of solid particles and gases, causing discomfort in the inhabitants and inducing environmental effects. To conduct the investigation, the study area was characterized by an on-site visit in the different sectors of the parish. The monitoring was carried out at two strategic points, the first point was in the Niagara sector with coordinates (E 766106; N 9893374) and the second point was in the La Laguna sector with coordinates (E 766588; N 9895934), it was performed During the 24 hours for four days to determine the concentrations existing in the day and at night, with the help of the E-BAM team the data was obtained accurately and reliably. Once the monitoring data was obtained, a database was made that was tabulated and compared with the Ecuadorian Air Quality Regulations TULSMA, Book VI, Annex 4, the information obtained allowed to know the concentration levels of particulate material, which are within the maximum permissible limits according to current regulations. By comparing the two monitoring points, it was determined that in the Niagara sector, high concentrations of PM10 were obtained with 35 μg/m3 at 11:00 a.m. and at 20:00 p.m. with 33 μg/m3 and PM2.5 with a concentration of 36μg/m3 at 11:00 am, while in the sector of La Laguna it has a PM10 concentration of 82 μg/m3 at 11:00 am and at 16:00 pm 73 μg/m3 and PM2.5 at 13:00 p.m. with 80μg/m3, due to the different industrial activities and third-order access roads that the sector presents. It was necessary to make measurements in the different sectors of the parish and continuously to know the concentration of this pollutant and evaluate its behavior in space and time, which allow to guide environmental control strategies, mitigation and follow-up by the competent environmental authorities.